Determination of Priority for Agricultural Irrigation Development District Level In North Sumatra Province Using the Analytical Hierarchy Process - Saud Hasiholan Saragih (Jurnal Mandiri IT, 2020)
The development of irrigation areas in North Sumatra is a decision-making process with many criteria (multi-criteria decision making) that requires a tool or method that can convert qualitative data into quantitative data and to be used in making decisions on these problems. AHP (Analytical Hierarchy Process) is a method that can be used to determine the ranking or hierarchy of various alternatives that are the subject of discussion. The AHP method decomposes complex multi-criteria problems into a hierarchy that performs measurements to find the ratio scale of pairwise comparisons, both for discrete and continuous data. The AHP stage is to define the problem to be discussed, Then a hierarchical structure (levels) is made by making general goals as the beginning of making the hierarchy and then continuing with sub-goals, criteria and possible alternatives at the bottom of the hierarchy. The next step is to create a pairwise comparison matrix for each pair of elements and criteria that are the topic of discussion. These comparisons can be taken from actual measures or basic scales that reflect the strength of the decision maker's feelings and relative preferences.